The impact of Feng Shui on residential property prices in western cultures - Bond, Sandy (Emerald Group Publishing Limited, 2008)
Purpose – To determine if the ancient Chinese tradition of Feng Shui affects residential property prices in a Western setting (‘‘Western’’ and ‘‘the West’’ refers to the cultures and peoples of the mainlands Europe, the Americas, Australia, and New Zealand.) Design/methodology/approach – Two approaches were adopted to measure the impact of Feng Shui design principles on property prices. First, a case study approach using a paired sales analysis was adopted to compare sales transaction prices of Feng Shui designed condominiums with sales prices of condominiums that were built without this design feature. Second, sales transaction data were analysed using multiple regression analysis in a hedonic pricing framework. Findings – The results were mixed but provide preliminary evidence that Feng Shui impacts positively on property prices in the West. Research limitations/implications – Firstly, the units were sold as ‘‘designer ready’’. Prices for these units exclude floor coverings, painting, kitchen and bathroom fittings, appliances, counter tops and plumbing fixtures. A more precise adjustment was not able to be made as the actual build-out cost for each unit was not available. However, it was felt that the average rate was a reasonable proxy for the cost of a build-out. Secondly, the case study includes sales of Feng Shui designed units in only one building. A more reliable result would have been achieved had the data set included several buildings constructed using the principles of Feng Shui. Practical implications – With the rise in popularity of the use of Feng Shui design in Western homes, understanding the effects of this on property values is important to both property valuers and investors of such property. Originality/value – Research on the impact of cultural beliefs on residential property values in the West is limited. This paper provides a contribution to understanding the value affects of such beliefs, specifically those relating to Feng Shui.